2010
DOI: 10.5607/en.2010.19.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like Effect of Kaempferol and Quercitirin, Isolated from Opuntia ficus-indica var. saboten

Abstract: Opuntia ficus-indica var. saboten. is widely cultivated in Jeju Island (South Korea) for use in manufacture of health foods. This study described antidepressant effect of two flavonoids (kaempferol and quercitrin) isolated from the Opuntia ficus-indica var. saboten. The expression of the hypothalamic POMC mRNA or plasma β-endorphin levels were increased by extract of Opuntia ficus-indica var. saboten or its flavoniods administered orally. In addition, antidepressant activity was studied using tail suspension t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…In a previous study, myricetin was reported to reduce the calcium-induced increase in oxidative metabolism in rat brain neurons when it was administered at 3 nM or greater (Oyama et al 1994). Additionally, kaempferol was reported to be useful for improving cognitive function due to its positive effects on depression, mood and cognitive functions (Park et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, myricetin was reported to reduce the calcium-induced increase in oxidative metabolism in rat brain neurons when it was administered at 3 nM or greater (Oyama et al 1994). Additionally, kaempferol was reported to be useful for improving cognitive function due to its positive effects on depression, mood and cognitive functions (Park et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, kaempferol was detected at lower concentrations (0.01-0.13 mg/100 g) in Australian jelly bush honeys, at 0.13-0.17 mg/100 g in New Zealand manuka honey (Yao et al 2003), 0.02-0.81 mg/kg in Malaysian honeys (Khalil et al 2011) and 0.01-0.099 mg/100 g in Polish honeys (Jasicka-Misiak et al 2012), but is slightly higher than the 0.00-3.01 mg/kg in honey samples from Bangladesh (Moniruzzaman et al 2014). Additionally, kaempferol was reported to be useful for improving cognitive function due to its positive effects on depression, mood and cognitive functions (Park et al 2010). Additionally, kaempferol was reported to be useful for improving cognitive function due to its positive effects on depression, mood and cognitive functions (Park et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This difference in the two animal models could be attributed to the different situations the animal has been exposed to in the tests; where the TST involves free suspension in the air; and FST involves exposure to water under experimental conditions. [27][28][29][30] Both these animal models suggest that the mobility is associated with the depressive state of the animal. 27,[31][32][33] It is known from previous research that the effect of different antidepressant treatments were not merely due to the stimulation of motor activity because this effect was observed even at doses that otherwise decreased activity in the open field test.…”
Section: Discussionmentioning
confidence: 99%
“…flower extract WS 1261 on mental and psychic a pilot study [17]. These findings encouraged the initiation of a trial on the effects of Sokatin in humans with symptoms of subsyndromal fatigue.…”
Section: -566mentioning
confidence: 99%